2020
DOI: 10.2516/ogst/2020006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of new insulation coatings for lean burn spark-ignited engines

Abstract: Clean and highly efficient internal combustion engines will still be necessary in the future to meet the ambitious CO2 emissions reduction targets set for light-duty vehicles. The maximal efficiency of stoichiometric Spark-Ignited (SI) gasoline engines has been steadily increasing in recent years but remains limited by the important relative share of cooling losses. Low heat rejection engines using ceramic barrier coatings have been presented in the past but smart insulation coatings are gaining a renewed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…A similar TBC study based on a direct injection gasoline engine 51 revealed another aspect of the surface structure, namely that increased piston surface roughness without TBC coatings does not cause an increase in unburned hydrocarbon emissions, while the open pores of a barrier coated material with the same surface roughness do cause a significant increase in unburned hydrocarbon emissions.…”
Section: Characteristics Of Thermal Barrier Coatingsmentioning
confidence: 92%
See 1 more Smart Citation
“…A similar TBC study based on a direct injection gasoline engine 51 revealed another aspect of the surface structure, namely that increased piston surface roughness without TBC coatings does not cause an increase in unburned hydrocarbon emissions, while the open pores of a barrier coated material with the same surface roughness do cause a significant increase in unburned hydrocarbon emissions.…”
Section: Characteristics Of Thermal Barrier Coatingsmentioning
confidence: 92%
“…Chérel et al 51 investigated thermal barrier effects with five different coating strategies based on ceramics and polymer/quasi-crystal composites applied by an APS process, summarized in Table 3. The TBC was applied to the piston in cases A to D and to the piston and head in case E. The authors used a modern supercharged gasoline direct-injection (GDI) engine with 200 bar injection pressure, 14:1 compression ratio, and 2.4 tumble ratio.…”
Section: Heat Insulation Effects Of Thermal Barrier Coatingsmentioning
confidence: 99%
“…724084). 36 Finally, the results obtained with the coated engine are compared with those of the base aluminium engine in order to quantify the impact of the thermal insulation material.…”
Section: Methodsmentioning
confidence: 99%
“…The above cited problems are resolved by applying anti-friction coatings and composite materials [16][17][18].…”
Section: Introductionmentioning
confidence: 99%